Sosialisasi Kepada Masyarakat: Penerapan Strategi Pemasaran Terhadap Peningkatan Pendapatan pada Wisata Bukit Condong - Elysa Octadina; Irma Aulia Saputri; Jusman; Reski Permana; Syafrizal; Wina Sapriyanti (Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2022)
The purpose of this service activity is to provide socialization to the community in implementing the Bukit Condong marketing strategy in order to increase the number of domestic and non-domestic tourist visits. The implementation of this service activity carried out by the author uses interview survey methods and direct discussions and observations as well as discussions with the community. From the results of the activities and analyzed descriptively using the marketing concept, it was concluded that tourism objects have the greatest marketing potential in providing customer satisfaction, so they are worthy of being promoted and marketed in the national tourism market in particular.